2021
DOI: 10.3390/brainsci11101313
|View full text |Cite
|
Sign up to set email alerts
|

Is Developmental Dyslexia Due to a Visual and Not a Phonological Impairment?

Abstract: It is a widely held belief that developmental dyslexia (DD) is a phonological disorder in which readers have difficulty associating graphemes with their corresponding phonemes. In contrast, the magnocellular theory of dyslexia assumes that DD is a visual disorder caused by dysfunctional magnocellular neural pathways. The review explores arguments for and against these theories. Recent results have shown that DD is caused by (1) a reduced ability to simultaneously recognize sequences of letters that make up wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 273 publications
(506 reference statements)
1
9
0
Order By: Relevance
“…Imaging studies on dyslexics have found abnormalities within the temporooccipital area, suggesting their importance in the complex cognitive process of reading (Bailey et al., 2018 ; Martin et al., 2016 ; Schurz et al., 2015 ; Ting et al., 2017 ). In fact, several studies have demonstrated that reading difficulties in dyslexia may be due to visual processing deficits, rather than phonological problems (Werth, 2021b ). Even pediatric patients with severe dyslexia demonstrate the ability to read pseudowords if given sufficient fixation time, suggesting they may require greater time for temporal summation, a process that occurs early in visual processing (Cheng et al., 2018 ; Werth, 2019 , 2021a , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging studies on dyslexics have found abnormalities within the temporooccipital area, suggesting their importance in the complex cognitive process of reading (Bailey et al., 2018 ; Martin et al., 2016 ; Schurz et al., 2015 ; Ting et al., 2017 ). In fact, several studies have demonstrated that reading difficulties in dyslexia may be due to visual processing deficits, rather than phonological problems (Werth, 2021b ). Even pediatric patients with severe dyslexia demonstrate the ability to read pseudowords if given sufficient fixation time, suggesting they may require greater time for temporal summation, a process that occurs early in visual processing (Cheng et al., 2018 ; Werth, 2019 , 2021a , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that reading difficulties in dyslexia may be due to visual processing deficits, rather than phonological problems (Werth, 2021b ). Even pediatric patients with severe dyslexia demonstrate the ability to read pseudowords if given sufficient fixation time, suggesting they may require greater time for temporal summation, a process that occurs early in visual processing (Cheng et al., 2018 ; Werth, 2019 , 2021a , 2021b ). Furthermore, it has been demonstrated that the fusiform gyrus plays a significant role in the ability to recognize words and pseudowords (Werth, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the German ophthalmologist Oswald Berkhan [ 1 ] first described the symptoms of dyslexia in 1881 and Rudolf Berlin introduced the term ”dyslexia“ [ 2 ], numerous theories have been proposed about its causes and treatments, [ 3 , 4 ] (for review). The magnocellular theory of dyslexia [ 5 , 6 , 7 , 8 , 9 ], the theory of unusual foveal and parafoveal processing of letters including an unusual crowding effect [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], and the temporal summation theory [ 20 , 21 , 22 , 23 ] regard developmental dyslexia (DD) as a visual perceptual disorder. Other theories assume that DD results from an impaired ability to process auditory stimuli [ 24 , 25 , 26 , 27 ] or is caused by impaired control of reading eye movements [ 6 , 7 , 8 , 9 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of dyslexia is still controversial and has been attributed to phonological, auditory or visual alterations [ 3 , 4 ]. A number of neuroimaging investigations focused on the central nervous system (CNS) have been performed so far to study normal [ 5 ] and abnormal reading process [ 2 , 6 ], and also reading interventions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%